Spectacular flops : game-changing technologies that failed - Schiffer, Michael B. (Eliot Werner Publications, Inc., 2019)
"Many technologies begin life as someone's vision of an ambitious, perhaps audacious, technology that is expected to have a revolutionary impact on consumers--whether families, companies, or societies. However, if that highly touted technology fails "prematurely" at some point in its life history, it becomes a spectacular flop. Employing a behavioral perspective, this book presents a sample of twelve spectacular flops encompassing the past three centuries, ranging from the world's first automobile to the nuclear-powered bomber. Because technologies may fail from many different causes, spectacular flops pose a special challenge to the author's long-term project of furnishing generalizations about technological change. Instead of constructing generalizations that apply to all spectacular flops, this book provides limited generalizations that pertain to particular groups of technologies bounded by parameters such as "long-term development projects" and "one-off projects." The reader need have no prior familiarity with the technologies because basic principles are introduced as needed"--